Hukum Musik dalam Islam: Analisis Penafsiran Quraish Shihab dalam Tafsir al-Misbah Al Misbah - Setiyo, Eko; Rosowulan, Titis; Purwanto, Purwanto; Mustofa, Ahmad (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
Research on music law has become an exciting and in-depth research topic, where researchers try to understand views and approaches to music from various perspectives, both in terms of fiqh, Islamic Sufism, hadith, and the thoughts of Islamic figures. From the research that has been carried out previously, there has not been much research on music that examines the interpretation of al Misbah by Quraish Shihab. The methodology applied is a qualitative approach, which aims to understand and explain specific meanings, phenomena, or ideas, different from quantitative approaches, which focus on statistics. This research uses a type of research library research (library research) using library sources. This research is qualitative research that explains descriptively using two data sources, namely primary and secondary. The primary source in this research is Tafsir al-Misbah, written by Quraish Shihab. Secondary data sources in this research come from books and journals relevant to the research theme. The data that has been collected is then analyzed carefully using thematic interpretation theory. The main findings show that the analysis of the verses used as the evidence or basis for the prohibition of music in the interpretation of al Misbah can be concluded that no verses expressly prohibit music. Based on the explanation above, the words "lahw al-hadith" in Surah Luqman verse 6 are one of the bases for the ulama who prohibit singing. However, Quraish Shihab supports the view that singing, including music, is acceptable in Islam if its content does not conflict with religious teachings and if the music promotes goodness.